2007
DOI: 10.1128/jcm.00140-07
|View full text |Cite
|
Sign up to set email alerts
|

Is the Volume of Blood Cultured Still a Significant Factor in the Diagnosis of Bloodstream Infections?

Abstract: "The higher the volume of blood cultured the higher the yield of blood cultures" has been a well-accepted dictum since J. A. Washington II performed his classic work. This rule has not been questioned in the era of highly automated blood culture machines, nor has it been correlated with clinical variables. Our objective in this study was to complete a prospective analysis of the relationship between blood volume, the yield of blood cultures, and the severity of clinical conditions in adult patients with suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 22 publications
3
98
1
5
Order By: Relevance
“…In this study, the overall incidence of positive results of 9.2% was lower than the internationally reported rate of 21.5-24.5% (Gonsalves et al, 2009;Bouza et al, 2007). A probable explanation could be due to the increased risk of mortality in patients with bacteraemia, in which there is generally a lower threshold for drawing blood culture samples, which increased our denominator (Bates and Goldman, 1991).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In this study, the overall incidence of positive results of 9.2% was lower than the internationally reported rate of 21.5-24.5% (Gonsalves et al, 2009;Bouza et al, 2007). A probable explanation could be due to the increased risk of mortality in patients with bacteraemia, in which there is generally a lower threshold for drawing blood culture samples, which increased our denominator (Bates and Goldman, 1991).…”
Section: Discussioncontrasting
confidence: 66%
“…Each inoculated bottle was weighed to two decimal places using a digital balance. The volume of blood in each bottle was calculated by subtracting the weight of the uninoculated bottle from the weight of inoculated bottle as described previously (Bouza et al, 2007), and the density of blood was assumed to be 1 (Lingwood et al, 2006). All bottles were incubated at 35°C in asemi-automated BACTEC system (BD Diagnostics) and monitored for a positive signal over a five-day period.…”
Section: Methodsmentioning
confidence: 99%
“…This is most likely a direct consequence of giving ciprofloxacin as prophylaxis, which effectively prevents bacteraemia due to Gram-negative bacilli, while giving selective advantage to the less susceptible Grampositive bacteria. 18 The blood cultures of 5 of the 10 patients with bacteraemia yielded two bacterial species that might simply reflect greater sampling efficiency, as we obtained a total of 70 ml of blood for blood cultures, which is more than others report 19 Viridans streptococci are primarily oral commensal flora; however, molecular analysis of the microbiota in the stomach shows that these bacteria can be found in large numbers along with Helicobacter pylori. 20 In children treated for AML, there was an association between the presence of gastrointestinal toxicity and the development of viridans group streptococcal bacteraemia.…”
Section: Discussionmentioning
confidence: 83%
“…Some previous studies focused on the potential benefit of keeping anaerobic bottle on board though anaerobe recoveries were not high, anticipating the growth of facultative anaerobes like staphylococci, streptococci, and some members of the family Enterobacteriaceae. However, it was observed that the amount of blood injected per bottle was associated with a better growth yield, this argues against the routine anaerobic bottles use, which is if the blood volume was saved for aerobic bottles [14,15]. Only one patient in the 4 discordant paired bottles grew an organism that called for intervention by a clinician.…”
Section: Discussionmentioning
confidence: 99%